Altered glucocorticoid metabolism in girls with central obesity. (1st May 2021) - Kim, Shin-Hye; Kim, Si-Eun; Choi, Man Ho; Park, Mi Jung
Abstract: Background: Dysregulation of glucocorticoid metabolism is known to be a causative factor of obesity. However, only a few studies have evaluated the enzymatic activities involved in glucocorticoid metabolism in the pediatric population. Objective: To examine whether circulating glucocorticoid metabolites and their ratios reflecting the activities of metabolic enzyme are associated with obesity and body composition in girls. Methods: A total of 227 girls aged 7–13 years (131 control, 45 overweight, 51 obese) were enrolled in this study. Serum concentrations of glucocorticoids (11-deoxycortisol, cortisol, tetrahydrocortisol [THF], allo-THF, allo-dihydrocortisol [allo-DHF], and cortisone) were evaluated by gas chromatography-mass spectrometry. Enzyme activities corresponding to the ratios of cortisol and cortisone to their respective precursors and metabolites were also assessed. Results: Serum levels of allo-THF were significantly higher in obese girls compared with those in overweight and control girls ( P  = 0.018); however, concentrations of other cortisol metabolites were not significantly different between the groups studied. According to the severity of obesity, increasing trends in the metabolic ratios reflecting the activity of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) [(cortisol + allo-DHF + allo-THF + THF)/cortisone], relative 5α/5β-reductase [allo-THF/THF] activity, and 3α-HSD [allo-THF/allo-DHF] activity, were noted ( P-for-trend <0.05). Body fat percentage and waist-to-height ratio positively correlated with the activities of 11β-HSD1 and 3α-HSD ( P  < 0.05). Following covariate control, girls with central obesity demonstrated significantly higher metabolic ratios reflecting 11β-HSD1, relative 5α/5β-reductase, and 3α-HSD activities ( P  < 0.05). Conclusions: We found an altered glucocorticoid metabolism suggesting increased production of cortisol by 11β-HSD1 and increased metabolic clearance of cortisol catalyzed by 3α-HSD in girls with central obesity. Highlights: Glucocorticoid metabolism dysregulation is implicated as a mediator in obesity. Serum concentrations of glucocorticoids and enzyme activities were assessed. Increased 11β-HSD and 3α-HSD activities were linked with central obesity in girls.